Assessment of cellular reduced glutathione content in Pseudokirchneriella subcapitata using monochlorobimane - Machado, Manuela D. (2017)
The green alga Pseudokirchneriella subcapitata has been extensively used for the assessment of adverse impacts of pollutants. Glutathione is involved in antioxidant defence and drug detoxification. Intracellular reduced glutathione (GSH) concentration can be used as an indicator of the health of cells. This work describes a simple and fast fluorescent cell-based assay for the evaluation of intracellular GSH in the alga P. subcapitata, using monochlorobimane (mBCl). Metabolically active algal cells incubated with 50 μmol L−1 mBCl form fluorescent bimane–glutathione (B-SG) adducts that can be measured fluorometrically. The distribution of GSH (B-SG adducts) in whole cells can be observed by epifluorescence microscopy, in the form of blue fluorescent spots. Depletion of cellular GSH with iodoacetamide, inhibition of glutathione S-transferase with ethacrynic acid or heat-induced death of the cells inhibited the formation of fluorescent adducts in the presence of mBCl. The fluorometric assay, using the 96-well microplate format, was able to detect GSH depletion in algal cells. This cell-based assay can be used to evaluate decreases in GSH content due to exposure to toxicants. This assay is amenable to automation and may be useful in high-throughput toxicity screening using the alga P. subcapitata.